Geographic and socioeconomic equity in PHC performance among the elderly in three Nordic countries. (20th October 2021) - Satokangas, M; Arffman, M; Agerholm, J; Hougaard, CØ; Andersen, I; Burström, B; Keskimäki, I
Abstract: : Denmark, Finland, and Sweden pursue equity in health for their citizens through universal health care. It is however unclear if these services reach the elderly population equally between different socioeconomic positions (SEP) or living-areas. Our aim was to assess both socioeconomic and geographic equity in primary health care (PHC) performance among the elderly 2000-2015 in the City of Copenhagen, Metropolitan Area of Helsinki, and Stockholm County. Hospitalisations for ambulatory care sensitive conditions (ACSC) was applied as a proxy for PHC performance. Hospitalization data for population aged ≥45 was acquired from the Danish National Patient Register, Finnish Care Register HILMO and patient administrative register from Stockholm County Council. Over time development of geographical variation in ACSC within each metropolis was analysed with Poisson multilevel models. These models were adjusted with individual SEP to distinguish between geographic and socioeconomic disparities. When compared to Stockholm, incidence rate ratios of ACSCs were higher both in Copenhagen (IRR 1.25; CI 95% 1.17-1.35) and in Helsinki (1.39; 1.30-1.49). While the average effect of time slightly decreased in each of the three capital regions (0.97; 0.96-0.98), this decrease was slightly more pronounced in Helsinki than in Stockholm (0.98; 0.97-0.99). Geographic variation in ACSCs seemed the highest both in Copenhagen and in Helsinki. Over time these variations seemed to reduce in Helsinki and in Stockholm, but not in Copenhagen. Adjusting for individual SEP seemed to explain a half of this variance in Helsinki and a third in both Stockholm and Copenhagen - after which over time geographic variation seemed to reduce also in Copenhagen. Geographic disparities in PHC performance among the elderly seem to have narrowed in Finland and in Sweden but remained stable in Denmark. However, in Denmark this seems to rather reflect socioeconomic disparities than stagnant development of PHC. Key messages: Despite the universal health care in Denmark, Finland and Sweden, there seems to persist both socioeconomic and geographic disparities in PHC performance among their elderly populations. Among the elderly, over time geographic disparities in PHC performance seem to have improved in both Finland and Sweden – but stagnated in Denmark due to the socioeconomic disparities.